2019
DOI: 10.1029/2018ef001087
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Satellite Solar‐Induced Chlorophyll Fluorescence to Meteorological Drought

Abstract: Solar‐induced chlorophyll fluorescence (SIF) could provide information on plant physiological response to water stress (e.g., drought). There are growing interests to study the effect of drought on SIF. However, to what extent SIF responds to drought and how the responses vary under different precipitation, temperature, and potential evapotranspiration conditions are not clear. In this regard, we evaluated the relationship between satellite‐based SIF product and four commonly used meteorological drought indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 88 publications
(122 reference statements)
4
46
1
Order By: Relevance
“…SIF is closely related to the photosynthesis of vegetation and can be used to monitor the physiological state of vegetation and water stress status [64]. When drought occurs, water stress will cause changes in the physiological state of vegetation, and this change will inevitably lead to changes in SIF [29], [33], [65]. However, there are still some limitations.…”
Section: E the Limitation Of Sif For Drought Monitoringmentioning
confidence: 99%
“…SIF is closely related to the photosynthesis of vegetation and can be used to monitor the physiological state of vegetation and water stress status [64]. When drought occurs, water stress will cause changes in the physiological state of vegetation, and this change will inevitably lead to changes in SIF [29], [33], [65]. However, there are still some limitations.…”
Section: E the Limitation Of Sif For Drought Monitoringmentioning
confidence: 99%
“…Previous studies based on three different global GPP products reported that the impact of drought on terrestrial primary production was underestimated by satellite-based LUE GPP models (Turner et al 2005;Mu et al 2007;Sims et al 2008). The reason for the underestimation is that these GPP models did not simulate the water balance, or did not account for the direct effects of soil moisture in addition to VPD and changes in greenness (Jiao et al 2019a;Stocker et al 2019). Our study found that GPP VPM computed with T opt−s for the years with higher precipitation showed a greater improvement than for the years with lower precipitation (figure S5).…”
Section: Siteidmentioning
confidence: 99%
“…Global warming and climatic extremes (e.g. heatwaves and cold spills) have large impacts on vegetation production across space and time (Mu et al 2011;Jiao et al 2019a;Ryu et al 2019). Accurately quantifying the effects of air temperature on the GPP of vegetation at local, regional, and global scales is critical to improving the modeling of GPP and terrestrial carbon cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies did not consider more than three variables, thereby somewhat circumventing this problem while ignoring potentially important variables (Seddon et al, 2016;Garonna et al, 2018;Claessen et al, 2019;Li & Xiao, 2020). Machine learning methods such as random forests have no assumptions on the input data characteristics, and are designed to process large amounts of diverse input data (Breiman 2001;Forkel et al 2019;Jiao et al 2019). Though they are also challenged by the collinearity in the input data, they are better placed to deal with this than traditional statistical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Jung et al 2020), reliable observation-based global photosynthesis proxies are only available for recent years through satellite-derived suninduced fluorescence (SIF, Baker et al, 2008;Frankenberg et al, 2011;Joiner et al,2013). SIF data is increasingly used to study the relationships between global vegetation productivity and hydro-meteorological drivers (Yang et al, 2015;Ying et al, 2015;Wagle et al, 2016;Zuromski et al, 2018;Jiao et al, 2019;Walther et al, 2019;Li & Xiao, 2020). Besides, spectral vegetation indices and biophysical parameters from multi-spectral satellite instruments such as the Moderate Resolution Imaging Spectroradiometer (MODIS) are widely used to study drivers of vegetation phenology and productivity (Forkel et al 2015;Seddon et al, 2016;Buermann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%